YEATS2 links histone acetylation to tumorigenesis of non-small cell lung cancer - Wenyi Mi (Nature Portfolio, 2017)
Histone modification recognition is an important mechanism for gene expression regulation in cancer. Here, the authors identify YEATS2 as a histone H3K27ac reader, regulating a transcriptional program essential for tumorigenesis in human non-small cell lung cancer.